Integrating Assessment with Teaching-learning of Science: an Experiment - PRABHA, SHASHI (THE PRIMARY TEACHER, 2014)
Integrating assessment with teaching-learning of science provides information about students’ existing ideas and to identify their learning gaps. It helps teachers to redesign teaching-learning experiences being responsive to their learning needs. Many teachers carry out a variety of assessment activities in the classroom during teaching-learning of science; however these are rarely used for formal assessment as recording each student’s performance remains a problem. Some experiments on the design of assessment activities were tried out by integrating assessment with teaching-learning in a science classroom. Two such experiments are reported in this paper. Very simple and practical ways of recording students’ performance are also presented. It was found that when assessment followed the flow of continuous dialogue and interaction with students, they moved beyond rote memorisation. These assessment activities helped students to focus more on what is to be learnt rather than worrying for their performance in paper-pencil test.